2018
DOI: 10.1155/2018/1020925
|View full text |Cite
|
Sign up to set email alerts
|

Increased CCR7loPD-1hiC

Abstract: T follicular helper cells (Tfh cells) affect essential immune pathogenesis in chronic hepatitis B virus (HBV) infection. The CCR7loPD-1hi Tfh subset has a partial Tfh effector phenotype and is associated with active Tfh differentiation, whereas the CCR7hiPD-1lo Tfh subset is a resting phenotype. We recruited 20 healthy volunteers and 77 patients with chronic HBV infection, including those in the immune tolerant (IT) phase (n=19), immune clearance (IC) phase (n=20), low replicative (LR) phase (n=18), and reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…However, in cHBV, IL-21 production in response to HBsAg peptides was decreased compared to acute infection [ 74 ]. Yet, an increased frequency of circulating Tfh was found and associated with HBeAg seroconversion as higher levels were detected in cHBV patients with HBeAg loss [ 74 , 75 , 76 ]. Furthermore, the Tfh from HBeAg seroconverters produced higher levels of IL-21 and harbored augmented frequencies of anti-HBe antibodies secreting B cells in vitro [ 75 ].…”
Section: Cd4 + T Cells In Chronic Hepatitis Bmentioning
confidence: 99%
“…However, in cHBV, IL-21 production in response to HBsAg peptides was decreased compared to acute infection [ 74 ]. Yet, an increased frequency of circulating Tfh was found and associated with HBeAg seroconversion as higher levels were detected in cHBV patients with HBeAg loss [ 74 , 75 , 76 ]. Furthermore, the Tfh from HBeAg seroconverters produced higher levels of IL-21 and harbored augmented frequencies of anti-HBe antibodies secreting B cells in vitro [ 75 ].…”
Section: Cd4 + T Cells In Chronic Hepatitis Bmentioning
confidence: 99%
“…In CHB patients, high expression of follicular helper T (Tfh) cell and CD4+ T cell C-X-C chemokine receptor type 5 (CXCR5) has been identified as positively correlated with immune activation. However, the understanding of the increased expression of chemokine receptors is limited (Huang et al, 2018). It has been shown that HBV infection does not affect the overall frequency of CD8 + CXCR5 + cells, while chronically infected patients accompanied with CD8 + CXCR5cells increased.…”
Section: Therapeutics That Modulate Chemokine Signaling Pathways To C...mentioning
confidence: 99%
“…Thus, the function of MZP B cells in supporting the migration of Tfh cells through CCR7 needs further confirmation. Notably, cTfh cells with low CCR7 expression are increased and have been described as an indicator in autoimmune diseases including AIH ( 148 ) and pSS ( 125 ), as well as chronic HBV infection ( 149 ). CCR7 int Tfh cells in the blood are closest to tonsillar Tfh lineage cells and exhibit a more potent capacity to induce memory B cells to differentiate into antibody-producing cells than CCR7 high Tfh cells ( 150 ).…”
Section: Novel Insights Into Breg-mediated Regulation Of Tfh and Tfr In Autoantibody Productionmentioning
confidence: 99%